Environmental ethics : what really matters, what really works - Schmidtz, David; Willott, Elizabeth, 1955- (New York : Oxford University Press, 2002)
"Featuring sixty-two accessible selections--from classic articles to examples of cutting-edge original research--Environmental Ethics: What Really Matters, What Really Works addresses both of the principal areas of inquiry in the field: the exploration of morality from an environmental perspective and the analysis of the current state of our environment. Aiming to determine what issues really matter, the first section of the book responds to such questions as: What is value? What types of things have value? Is the value of a human being fundamentally different from the kind of value we find elsewhere in nature? What role do consumer goods and services play in a good life? and Is there room for environmental consciousness in a good life? The second section turns to the question of what it would take to solve our environmental problems. It strives to go beyond the "hype" to present informed perspectives on the true nature of those problems and investigates important questions like: What is causing or exacerbating these problems? and What solutions have been tried? The selections present philosophical, biological, and social scientific approaches to the major issues. Environmental Ethics features first-hand descriptions from people who have actually been involved in such projects as wildlife management in Africa, ecofeminist initiatives in India, and radical activism on the high seas. It also provides up-to-date data on population issues and community-based wildlife initiatives. Ideal for undergraduate courses in environmental ethics, environmental issues, and applied ethics, this unique text will also be a helpful resource for graduate students and professors, as it retains most of the footnotes from the original articles." http://www.loc.gov/catdir/enhancements/fy0612/2001021210-d.html.
The dawn of reverence. Moment on the Earth / Gregg Easterbrook -- Thinking like a mountain / Aldo Leopold -- Historical roots of our ecological crisis / Lynn White, Jr. -- Animal liberation and the land ethic. All animals are equal / Peter Singer -- Land ethic / Aldo Leopold -- Values in and duties to the natural world / Holmes Rolston III -- Animal liberation and environmental ethics: bad marriage, quick divorce / Mark Sagoff -- Extending the realm of rights. Should trees have standing? Toward legal rights for natural objects / Christopher D. Stone -- Rights of animals / Joel Feinberg -- Good of trees / Robin Attfield -- Duties concerning islands / Mary Midgley -- Species equality and respect for nature. Ethics of respect for nature / Paul W. Taylor -- Are all species equal? / David Schmidtz -- Environmental holism. How to worry about endangered species / Tom Regan -- Biocentric individualism / Gary Varner -- Deep ecology / Bill Devall and George Sessions -- Social ecology versus deep ecology / Murray Bookchin -- Why do species matter? / Lilly-Marlene Russow -- Philosophical problems for environmentalism / Elliott Sober -- How wild does nature have to be? What's wrong with plastic trees? / Martin H. Krieger -- Call of the wild / Eric Katz -- Ecological restoration and the culture of nature / Andrew Light -- Rethinking the good life. Ideals of human excellence and preserving natural environments / Thomas E. Hill Jr. -- Redefining the good life in a sustainable society / Lester W. Milbrath -- Do we consume too much? / Mark Sagoff -- Letting the world grow old: an ethos of countermodernity / Freya Mathews -- Ecofeminism in theory and practice. Feminism and ecofeminism / Kristen Hessler and Elizabeth Willott -- Power and the promise of ecological feminism / Karen J. Warren -- Women, poverty, and population: issues for the concerned environmentalist / Gita Sen -- Women farmers of India's Deccan Plateau: ecofeminists challenge world elites / V. Rukmini Rao -- Human population. Future generations / Joel Feinberg -- Population, development, and the environment / Clark Wolf -- Recent population trends / Elizabeth Willott -- What it takes to preserve wilderness. Radical American environmentalism and wilderness preservation: a Third World critique / Ramachandra Guha -- Headaches and heartaches: the elephant management dilemma / Ian J. Whyte -- At the hand of man: peril and hope for Africa's wildlife / Raymond Bonner -- When preservationism doesn't preserve / David Schmidtz -- Sustainable use and institutional structure. Tragedy of the commons / Garrett Hardin -- Approximate optimality of aboriginal property rights / Martin J. Bailey -- Environmental lessons / Carol Rose -- Institution of property / David Schmidtz -- Poverty as an environmental problem. Living on a lifeboat / Garret[t] Hardin -- Famine, affluence, and morality / Peter Singer -- Global environment and international inequality / Henry Shue -- Feeding people versus saving nature / Holmes Rolston III -- Natural enemies: an anatomy of environmental conflict / David Schmidtz -- Vanishing resources. Designing cities and buildings as if they were ethical choices / Jessica Woolliams -- Why the good news shouldn't scare you / Gregg Easterbrook -- Doomslayer / Ed Regis -- Good news, in perspective / Paul Ehrlich and Anne Ehrlich -- Cost-benefit analysis and environmental policy. Cost-benefit analysis: an ethical critique / Steven Kelman -- Cost-benefit analysis defended / Herman B. Leonard and Richard J. Zeckhauser -- Moral pluralism and the environment / Andrew Brennan -- Place for cost-benefit analysis / David Schmidtz -- Environmentalism in practice. Environmentalists' dilemma: dollars and sand dollars / Bryan G. Norton -- Fragile freedoms / Bryan G. Norton -- Therapeutic nihilism and environmental management / Eugene C. Hargrove -- Mad cowboy: the cattle rancher who won't eat meat / Howard F. Lyman with Glen Merzer -- Tora! Tora! Tora! / Paul Watson -- Missing shade of green / Kate Rawles -- Environmental philosophy is environmental activism: the most radical and effective kind / J. Baird Callicott -- Taking environmental ethics public / Andrew Light.
Includes bibliographical references.
Keywords: Environmental ethics